Field Experience A Reflective Practice in Education - Venugopal, Kalpana (INDIAN EDUCATIONAL REVIEW, 2013)
This is a qualitative paper employing the narrative style of reporting a field experience in school from a reflective perspective. It delineates the objectives and the methodology adopted; elaborates the field activities undertaken and discusses the reflective gains from this practice to education-both that of learning and teaching and the learner and teacher.